Efforts for early detection of growth and development of children aged 4-5 years through health screening activities at RA IT Nurul Islam Semarang - Asykira, Azka; Mustakimah, Mustakimah; Mushlih, Ahmad (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: The golden age phase is the most critical period for closely monitoring children's growth and development through health screening activities. Early detection of children's growth and development conditions is essential to prevent and address potential health and developmental issues. Early intervention can reduce the negative impact of developmental problems.Aim: This research aims to determine the results of early detection of the growth and development of children aged 4-5 years to identify any developmental disorders or deviations and nutritional status in RA IT Nurul Islam Semarang as early as possible.Method: This research design uses quantitative research. Data collection techniques include observation, interviews, and documentation.Results: The results of the growth and development detection in children showed that 7 children had normal nutritional status, 4 were overweight, 1 was underweight, and 3 were obese. This research indicates that early detection of children's growth and development requires periodic and further health screenings to prevent deviations or problems in children's growth and development.Conclusion: Educators, teachers, health workers, and other professionals can identify children at risk of developmental delays based on reports from parents or suspicions from teachers. Teachers' suspicions about developmental problems or deviations in school children should be followed up with early intervention efforts for optimal early childhood growth and development detection